2011
DOI: 10.1002/jor.21476
|View full text |Cite
|
Sign up to set email alerts
|

New treatment for peripheral nerve defects: Reconstruction of a 2 cm, monkey median nerve gap by direct lengthening of both nerve stumps

Abstract: ABSTRACT:We have developed a new treatment for peripheral nerve defects: nerve-lengthening method, and confirmed the efficacy and safety of our method using cynomolgus monkeys. A 20-mm defect in the median nerve of monkey's forearms was repaired through the simultaneous lengthening of both nerve stumps with original nerve-lengthening device. To evaluate nerve regeneration after neurorrhaphy, electrophysiological, histological, and functional recovery were examined and compared to the standard autografting. Ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…At the time of analysis of this review, only 37 studies had reached completion. [16][17][18][19][20]23,30,32,36,38,[41][42][43]49,50,[52][53][54][57][58][59][60][61][62][63][64][65][66][67][68][69]71,76,80,83,86,93,94,97,105,106 Among these, only 8 studies updated their registration and published articles containing results after the primary completion date of the studies. 32,56,58,59,61,62,64,106 No results were reported for 32 studies.…”
Section: Results Reporting Of Completed Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…At the time of analysis of this review, only 37 studies had reached completion. [16][17][18][19][20]23,30,32,36,38,[41][42][43]49,50,[52][53][54][57][58][59][60][61][62][63][64][65][66][67][68][69]71,76,80,83,86,93,94,97,105,106 Among these, only 8 studies updated their registration and published articles containing results after the primary completion date of the studies. 32,56,58,59,61,62,64,106 No results were reported for 32 studies.…”
Section: Results Reporting Of Completed Studiesmentioning
confidence: 99%
“…32,56,58,59,61,62,64,106 No results were reported for 32 studies. [16][17][18][19][20]23,30,36,38,[41][42][43]49,50,[52][53][54]57,60,63,[65][66][67][68][69]76,80,86,93,94,97,105 Comparative Analysis A multiple linear regression analysis was conducted to ascertain determinants influencing the likelihood of project completion. Four regression models were sequentially refined, with the independent variables evaluated being RCT, single blinding, industry, phase 2, and several others that were ultimately excluded.…”
Section: Results Reporting Of Completed Studiesmentioning
confidence: 99%
“…Several studies, including a modified version of our device, have demonstrated the feasibility of direct end-to-end repairs under tension (Hentz et al, 1993;Sunderland et al, 2004;Kechele et al, 2011;Howarth et al, 2019a). In addition, progressive lengthening over days to weeks followed by end-to-end repair also results in positive outcomes (Sharula et al, 2010;Hara et al, 2012;Howarth et al, 2019b;Howarth et al, 2020). However, beyond axonal densities and, occasionally, neuronal geometry, little quantification is provided on the morphological response to tension.…”
Section: Effects Of Strain On Regeneration Of Severed Nervesmentioning
confidence: 99%
“…Behavioral assessment, including animal behaviors, such as finger agility, digital opposition of thumb to index fingers, fist clenching, and food-gripping can be evaluated along with electrophysiological assessments, fluorogold retrograde tracing tests, and histological and morphometric analyses were used to assess recovery nerve function. In addition to nerve conduction studies, muscle contraction force and wet weight of the APB muscle, apple pinch test (thumb abduction during grasping assess via photo analysis), and gross observation and histological observation of nerve regeneration can also be used for evaluation [ 108 ]. However, this model has associated difficulty in locomotive observation due to loss of adduction and flexion function of the metacarpophalangeal joints of the thumb [ 101 , 109 ].…”
Section: Models By Nerve Typesmentioning
confidence: 99%